Political Reform in Indonesia after Soeharto - Crouch, Harold (Book collections on Project MUSE., 2010)
Three decades of authoritarian rule in Indonesia came to a sudden end in 1998. The collapse of the Soeharto regime was accompanied by massive economic decline, widespread rioting, communal conflict, and fears that the nation was approaching the brink of disintegration. Although the fall of Soeharto opened the way towards democratization, conditions were by no means propitious for political reform. This book asks how political reform could proceed despite such unpromising circumstances. It exa ...